Application of 3D Printing for Energy Storage Devices - Kandi R.; Mishra D.K.; Tripathi A. (My University, 2025)
In the last decades, the importance of energy storage devices (ESDs) as the main power source has become very vital in our fast-growing modern society. However, the traditional ESD already available in the market is not able to meet the demand of the current scenario of our daily life. The major concerns which are associated with traditional ESD are poor energy density, power density, unsafety, as well as lower cycle life of energy storage elements, resulting in weak performance. Therefore, ESD is not well balanced to fulfill the application requirements. Although, in recent trends, 3D printing (or Additive Manufacturing) techniques are found to be more advantageous in energy storage areas. Thus, different fabrication techniques of 3D printing that are used for manufacturing the structural electrodes of ESDs are summarized in this chapter, including the preparation of inks, 3D-printed resins, and 3D-printed electrodes. Moreover, the adoption of different materials for the fabrication of ESDs is also discussed. At the end of this chapter, we have discussed the future perspective of 3D printing technologies for the development of structural ESDs. We believe that promising 3D printing technologies are providing a better production route for the fabrication of structural ESDs for special load applications. © 2024 selection and editorial matter, Pawan Sharma and Vishvesh J. Badheka; individual chapters, the contributors.